Contexto brasileiro de ataques a bancos e custos com segurança privada - Araújo, Francisca Juliana de Andrade (2017)
Private security in Brazil emerged, legally, in 1969, motivated by the increase of criminal actions at banking braches, such as robberies and break-ins. In order to inhibit these offenses, The Decree 1,034 obligated the hiring or training of private security by financial institutions, including banks, economic boxes, their agencies and offices. Since then the banking institutions have been spending so much of high amounts with those services with personnel of safety as in the implementation of barriers to hinder to the actions Criminal. In that context, the research has as l aim at general investigated the relationship among costs with deprived safety and attacks to banks in Brazil. For so much, a research quantitative, exploratory, descriptive and documentary was accomplished, considering the temporary horizon from 2011 to 2015. Data on private security costs were collected directly from the financial statements of the banking institutions, and data on bank attacks were obtained through the semi-annual studies published by the National Confederation of Financial Sector Workers (Contraf-CUT).The data referring to the costs with private security were collected straightly of the financial demonstrations of the bank institutions, already the data relative to the attacks to banks were obtained through the studies semesters reported by the Confederação Nacional dos Trabalhadores do Ramo Financeiro (Contraf-CUT). The results indicated that the breakings in to banks in Brazil were still growing up to 2014, but in 2015 they suffered a reduction of 59 %, while the robberies grew up to 2013, fell in 2014, but they grew again in 2015. Regarding the attacks distribution for the country, the states of Pools, Laborer, Piauí, Rio Grande do Norte, Maranhão, Pernambuco and Mato Grosso predominated between the states with bigger rates of robberies and / or breakings in for agency. Already referring to second variable, the costs with security guard deprived in the bank institutions, when relative to the numbers of agencies, suffered a fall in 2012, however the next years they were still growing. The correlation of Pearson did not demonstrate significant relation between the variables, in other words, two hypotheses of the inquiry were rejected, since it is not possible to affirm that the costs with security guard deprived of the bank institutions are not even associated, statistically, with the robberies not even with the breakings in the banks in Brazil. The results of this study may impel future research both in relation to attacks on banks in the country and on private security costs through the inclusion of new factors that may influence the behavior of the studied variables and the replication of the research in other segments.